2022
DOI: 10.3389/fsurg.2022.965951
|View full text |Cite
|
Sign up to set email alerts
|

Mid and long-term overall survival after carcinologic resections of thyroid cancer bone metastases

Abstract: BackgroundBone metastases in thyroid cancer impair the patient's quality of life and prognosis. Interestingly, wide margins resection as the surgical treatment of bone metastases might improve the overall survival (OS). Nonetheless, data are lacking regarding the potential benefits of this strategy.MethodsIn order to assess the OS of patients with thyroid cancer after a bone metastases carcinologic resection, a retrospective multicentric study was performed, evaluating the 1, 5, 10 and 15 years-OS along with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…In terms of long-term oncological outcomes for patients who underwent radical resection of bone metastases from DTC, in the multicentric retrospective study conducted by Fragnaud et al, overall survival for patients who underwent wide resection at 1, 5, 10, and 15 years was 76.2%, 63.6%, 63.6%, and 31.8%, respectively [ 15 ]. This study described much higher overall survival rates in comparison to the studies of Nakayama et al and Satcher et al [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of long-term oncological outcomes for patients who underwent radical resection of bone metastases from DTC, in the multicentric retrospective study conducted by Fragnaud et al, overall survival for patients who underwent wide resection at 1, 5, 10, and 15 years was 76.2%, 63.6%, 63.6%, and 31.8%, respectively [ 15 ]. This study described much higher overall survival rates in comparison to the studies of Nakayama et al and Satcher et al [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study described much higher overall survival rates in comparison to the studies of Nakayama et al and Satcher et al [ 16 , 17 ]. Moreover, Fragnaud et al demonstrated that R0 and R1 resections were associated with a better prognosis compared to R2 resection, whereas the overall survival was extremely higher (82.3% vs 0%) when a resection of isolated bone metastasis was performed in comparison to patients with multi-metastatic bone lesions [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to patients with metastatic thyroid carcinoma to the appendicular skeleton, wide resection of solitary bone lesions have improved rates of survival, regardless of tumor subtype. [57][58][59][60] This is an important consideration as metastatic thyroid cancer may be less responsive to radiation and systemic therapy. 61,62 There is also data to suggest that resection of up to five osseous metastatic foci with negative margins also prolongs survival.…”
Section: Thyroid Carcinomamentioning
confidence: 99%
“…Они плохо отвечают на радиойодтерапию, и полная ремиссия костных метастазов составляет всего лишь 10-17 %. 8,9].…”
Section: Introductionunclassified